Facile strategy toward the development of novel binder and thickening agent from apple rock bael for textile printing - N. S. Elshemy; S. H. Nassar; Nancy S. Elhawary; Mona M. Ali (Scientific Reports)
Abstract This study focuses on isolating a natural binder and thickening agent derived from the Aegle marmelous fruit. The isolated natural gum can be effectively employed as a binder and thickening agent in fabric printing applications. The findings indicate that this natural gum has remarkable rheological characteristics, essential for achieving optimal printing results. Microwave irradiation techniques and thermal bonding, varying in duration, power, and temperature, were employed to fix the printed samples that utilized the isolated natural gum. The results demonstrated that printed textiles exhibited excellent color fastness, with samples treated via microwave fixation showing enhanced color saturation, as evidenced by higher K/S values. A thorough evaluation of the physical and mechanical properties was conducted, including assessments of color yield, uniformity, absorption, and fixing efficiency. The results indicate that both weight loss and water absorption tend to increase over time. The natural gum isolated from Aegle marmelous shows minimal loss and absorption, in contrast to commercial gum (Sodium alginate), which exhibits significantly higher levels. Scanning electron microscopy (SEM) highlights distinct differences in particle morphology between the two types of gum; the commercial variety presents spherical aggregates, while the isolated natural gum features elongated thread-like particles. Extended microwave exposure leads to enhanced color intensity, which is influenced by the fabric structure and type of gum used. The K/S value peaks at 70 watts and subsequently decreases at 90 watts for printed cotton and cotton/polyester blends, while printed wool achieves the best results at 50 watts for 60 s. Closed samples consistently show enhanced K/S values, irrespective of the microwave settings. Regarding thermo fixation, as fixation temperatures and duration increase, K/S values typically rise, except for printed cotton. The K/S values reached their maximum at 160 °C for 6 min for wool and polyester/cotton blends, whereas cotton peaked at 140 °C under the same conditions. The observed variations in color yield, penetration, and fixation percentages among the different fabrics are attributed to their unique chemical compositions and characteristics, as well as the effects of microwave irradiation. Furthermore, employing pulsed microwave irradiation helps regulate temperature and mitigate exothermic reactions, resulting in improved dye-fabric interactions and overall stability of the dyeing process. This thorough analysis highlights the potential of utilizing natural agents derived from Aegle marmelous in contemporary textile printing, supporting sustainable practices while upholding performance standards.